Optimal hemoglobin level for anemia treatment in a cohort of hemodialysis patients - Mi Yeon Jung; Soon Young Hwang; Yu Ah Hong; Su Young Oh; Jae Hee Seo; Young Mo Lee; Sang Won Park; Jung Sun Kim; Joon Kwang Wang; Jeong Yup Kim; Ji Eun Lee; Gang Jee Ko; et al. (The Korean Society of Nephrology, 2015)
Background: Anemia is a major risk factor that contributes to mortality in patients with chronic kidney disease. There is controversy over the optimal hemoglobin (Hb) target in these patients. This study investigated the association between Hb level and mortality in a cohort of hemodialysis (HD) patients in Korea. Methods: This study was a multicenter prospective observational study of maintenance HD patients that was performed for 5 years in western Seoul, Korea. Three hundred and sixty-two participants were enrolled. Laboratory values and mortality were accessed every 6 months. Repeated measures of laboratory values in each interval were averaged to obtain one semiannual mean value. The Hb values were divided into six groups: (1) Hb<9 g/dL; (2) 9 g/dL≤Hb<10 g/dL; (3) 10 g/dL≤Hb<11 g/dL; (4) 11 g/dL≤Hb<12 g/dL; (5) 12 g/dL≤Hb<13 g/dL; and (6) Hb≥13 g/dL. We analyzed the odds ratio for all-cause mortality, based on the Hb group, and adjusted for demographics and various laboratory values. Statistics were performed with SAS, version 9.1 software (SAS Institute Inc., Cary, NC, USA). Results: Mortality odds ratios relative to the reference group (10-11 g/dL) in the fully adjusted model were 3.61 for<9 g/dL; 3.17 for 9-10 g/dL⁎; 4.65 for 11-12 g/dL⁎; 5.50 for 12-13 g/dL⁎; and 2.05 for≥13 g/dL (⁎ indicates P<0.05). Conclusion: In this study, a Hb level of 10-11 g/dL was associated with the lowest mortality among the groups with Hb level<13 g/dL. Larger interventional trials are warranted to determine the optimal Hb target for Korean HD patients.